Bacterial Cell Wall Analogue Peptides Control the Oligomeric States and Activity of the Glycopeptide Antibiotic Eremomycin: Solution NMR and Antimicrobial Studies - László Izsépi; Réka Erdei; Anna N. Tevyashova; Natalia E. Grammatikova; Andrey E. Shchekotikhin; Pál Herczegh; Gyula Batta (MDPI AG, 2021)
For some time, glycopeptide antibiotics have been considered the last line of defense against Methicillin-resistant Staphylococcus aureus (MRSA). However, vancomycin resistance of Gram-positive bacteria is an increasingly emerging worldwide health problem. The mode of action of glycopeptide antibiotics is essentially the binding of peptidoglycan cell-wall fragments terminating in the d-Ala-d-Ala sequence to the carboxylate anion binding pocket of the antibiotic. Dimerization of these antibiotics in aqueous solution was shown to persist and even to enhance the antibacterial effect in a co-operative manner. Some works based on solid state (ss) Nuclear Magnetic Resonance (NMR) studies questioned the presence of dimers under the conditions of ssNMR while in a few cases, higher-order oligomers associated with contiguous back-to-back and face-to-face dimers were observed in the crystal phase. However, it is not proved if such oligomers persist in aqueous solutions. With the aid of 15N-labelled eremomycin using 15N relaxation and diffusion NMR methods, we observed tetramers and octamers when the N-Ac-d-Ala-d-Ala dipeptide was added. To the contrary, the N-Ac-d-Ala or (N-Ac)2-l-Lys-d-Ala-d-Ala tripeptide did not induce higher-order oligomers. These observations are interesting examples of tailored supramolecular self-organization. New antimicrobial tests have also been carried out with these self-assemblies against MRSA and VRE (resistant) strains.